(untitled) - Atabekov, V. (Moscow, 1980)
Chapter one. Electric power production, distribution, and utilization; chapter two. Organization of work, industrialized methods, and equipment used for installation and wiring; chapter three. General information on buildings and construction sites, ...
Keywords: Electric power distribution,Phân phối điện năng